Synthesis of Naphthoic Acids as Potential Anticancer Agents - Deck, Lorraine M.; Greenberg, Jacob A.; Whalen, Lisa J.; Vander Jagt, David L.; Royer, Robert E. (Synlett, 2019)
As part of ongoing research to investigate structural requirements for lactate dehydrogenase inhibition by highly substituted naphthoic acids, nine new aryl-substituted dihydroxynaphthoic acids were synthesized from three known precursors. Described here are efficient preparations of the 1-naphthoic acid target compounds by using Suzuki coupling reactions, formylations, oxidations, and demethylations. Lactate dehydrogenase inhibition studies conducted with five of the compounds revealed values of the inhibitory constant Ki in the low micromolar range.
Keywords: naphthoic acids; Suzuki coupling; naphthaldehydes; formylation; oxidation; medicinal chemistry